Desenvolvimento sustentável, organização e reorganização de trabalhadores rurais do alto rio Atuá na ilha de Marajó: exame de uma experiência - FERRÃO, Euzalina da Silva (2006)
This work aims analysing the ways by which sustainable development projects were introduced and implemented in the town of Muaná and in the High Atuá Region, in the Marajó Island, considering intervention of governmental and non-governmental organizations. Organization and reorganization processes of the rural workers at the High Atuá River in unions and associations are analysed, as well as the perception and strategy of those whom the projects are addressed to. The connection between such projects and recent forms of management such as Agenda 21, which is in process, is discussed.